The Effect Of Cash Turnover, Account Receivable Turnover And Inventory Turnover On Profitability - Fitria, Syifa Maulida; Suartini, Sri (Universitas Gorontalo, 2021)
This study aims to see the effect of the effect of turnover, transaction turnover and turnover on the inventory of automotive industry companies listed on the Indonesia Stock Exchange in 2014-2018 as measured by the return of assets either partially or simultaneously. The data analysis technique used in this research is multiple linear regression analysis techniques. The results showed that (1) partially the effect of cash turnover had no positive and insignificant effect on profitability (2) partially the effect of turnover had no positive and insignificant effect on profitability (3) partially the effect of inventory turnover had positive and positive effects significant to profitability.